THE DEVELOPMENT OF THAI ARTIFICIAL INTELLIGENCE CHATBOT FOR SUPPORTING ACADEMIC CONSULTANCY FOR TERTIARY STUDENTS - Nithiyuwith, Thinaphan; Treenuntharath, Tassanan (Life Sciences and Environment Journal, 2020)
In crisis era that makes student continuously decrease. The important way that helps solving the problem is having the good consulting system. This research aims 1) to study the dataset and knowledge base of the Thai artificial intelligence chat bot (TAICB) for supporting academic consultancy for tertiary students 2) to develop the TAICB for supporting academic consultancy for tertiary students and 3) to assess the performance of TAICB for supporting academic consultancy for tertiary students. This research was classified 3 steps 1) gathering data from 4 academic and registration and education evaluation directors of government and private university for developing the dataset and knowledge base of the TAICB. 2) developing the TAICB consists of the relationship database, ontology knowledge base, natural language processing concept and web interface to connect with the TAICB and 3) evaluating the performance of TAICB founded that the artificial intelligence chat bot has performance in answering question at accuracy rate 93.6% and users satisfied to the TAICB at high level.